Impact of Double-Intake Programmes on the Teacher Co-Efficient Determinant of Quality Education at the University of Nairobi, Kenya - Wanjala, Genevieve; Obutu, Ongosi Boni (International Journal of Educational Technology and Learning, 2020)
This research was carried out in order to determine the impact of double-intake programmes on the quality of education in the University of Nairobi in Kenya using the teacher coefficient measure. It had one objective and one research question. Using descriptive survey research design the target population consisted of 61,000 regular students enrolled in 43schools/faculties, 5,900 students in their fourth year of study and 2,000 teaching staff. Calmorin and Calmorin (2007) formula for scientifically determining sample size yielded a total of 489 respondents. Simple random sampling was used to select 251 fourth year students while stratified random sampling was used to select 238 teaching staff as actual respondents. Data were collected using questionnaires, document analysis, observation and interview. Quantitative and qualitative data analysis methods were used with the aid of statistical package for social sciences (SPSS) version 26.The findings show that the number of students admitted overwhelmed both the academic and non-academic staff members who served them because the university accepted to engage in double intake programmes without considering an increase in the number of the staff members and this skewed student to faculty ratio led to degenerated service provision. Consequently, the research recommends that the university plans adequately for the number of staff required versus the anticipated students to be enrolled in future since a compromise in the student to faculty ratio will definitely have a negative impact on the quality of education.